Sensitivity of Dynamic Methods for Damage Detection in Structural Concrete Bridges - M. Breccolotti; G. Franceschini; A.L. Materazzi (Shock and Vibration)
A critical analysis of the available methods for the assessment of structural concrete bridges through the observation of their dynamic response is carried out. A mathematical model for the evaluation of the natural frequencies shift due to bridge damage is applied to the case of an existing reinforced concrete bridge. The numerical results, along with the general structure of the mathematical problem, allow discussing some limitation and drawbacks of the dynamic methods. Namely the need for a reference set of the bridges dynamic properties before the onset of damage and the effect of the ambient temperature variation may lead, in many cases, to unreliable estimates of the structural condition of the investigated bridges.